2011
DOI: 10.1007/s00464-011-2077-3
|View full text |Cite
|
Sign up to set email alerts
|

Extending the limitations of liver surgery: outcomes of initial human experience in a high-volume center performing single-port laparoscopic liver resection for hepatocellular carcinoma

Abstract: Although the procedure requires a lot of technical expertise added to the skill of liver surgery, single-port laparoscopic liver resection for hepatocellular carcinoma seems a feasible approach in a variety of well-selected cases. In spite of the demanding nature of the procedure and the requirement of better instrumentation for single-port laparoscopic surgery, the results seem to compare favorably with conventional laparoscopic surgery and open surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 20 publications
1
56
0
1
Order By: Relevance
“…The small case series demonstrated that this technique is feasible in well-selected patients when performed by experienced laparoscopic hepatobiliary surgeons. All previous reports concluded that correct patient selection and laparoscopy experience are the most important part of a successful outcome [10][11][12][13][14][15].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The small case series demonstrated that this technique is feasible in well-selected patients when performed by experienced laparoscopic hepatobiliary surgeons. All previous reports concluded that correct patient selection and laparoscopy experience are the most important part of a successful outcome [10][11][12][13][14][15].…”
Section: Resultsmentioning
confidence: 99%
“…The benefits of SPL liver resection on a patient with cirrhosis have been demonstrated [4,10]. Single-port laparoscopic liver resection on a patient with cirrhosis has the main advantage of reduced postoperative deterioration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Las primeras publicaciones corresponden a lesiones benignas, ampliá ndose posteriormente al tratamiento de enfermedad maligna como metá stasis y hepatocarcinomas, con resultados similares a los de la laparoscopia convencional [21][22][23][24] .…”
Section: Discusió Nunclassified